New synonymies and new records of Afrotropical and Madagascan Pentatominae (Hemiptera: Heteroptera: Pentatomidae) - Kment, Petr; Jindra, Zdeněk; Rider, David A. (Zootaxa, 2014)
The following new synonymies within the family Pentatomidae, subfamily Pentatominae, are established: Aesula Stål, 1876 = Pseudacrosternum Day, 1965, syn. nov. (Nezarini), Aesula viridissima (Signoret, 1861) = Aesula signoretiana Kirkaldy, 1909, syn. nov. = Pseudacrosternum cachani Day, 1965, syn. nov. = Pseudacrosternum cachani var. scutellatum Day, 1965, syn. nov., and Andocides vittaticeps (Stål, 1858) = Andocides vittaticeps var. viridescens Schumacher, 1913, syn. nov. Afrania brachyptera (Schaum, 1853), stat. restit., is restored as the oldest available name for that species, with Afrania wahlbergi Stål, 1854, syn. restit., being its junior synonym. Lectotype of Pentatoma viridissima Signoret, 1861 is designated, and lectotype designation of Pseudolerida incerta (Schouteden, 1909) is commented. The following new or confirmed state records are provided: Cappaeini: Leridella kenyensis Jeannel, 1913 (Cameroon), Paralerida bolivari (Schouteden, 1904) (Republic of the Congo, Uganda), P. niokana Linnavuori, 1982 (Uganda), Tripanda (Tripanda) dispar Schouteden, 1964 (Cameroon, Ghana, Liberia), T. (T.) horacekorum Kment & Jindra, 2009 (Cameroon, Guinea), T. (T.) jurickorum Kment & Jindra, 2009 (Gabon, Ivory Coast), T. (T.) longiceps (Villiers, 1967) (Democratic Republic of the Congo, Gabon), T. (T.) signitenens (Distant, 1898) (Democratic Republic of the Congo, Mozambique), T. (Tenerva)       decorata (Jensen-Haarup, 1937) (Kenya, Oman, Tanzania); Carpocorini: Andocides vittaticeps (Angola); Diploxyini: Acoloba lanceolata (Fabricius, 1803) (Angola, Central African Republic, Zambia, Zimbabwe); Eysarcorini: Pseudolerida bitalensis Schouteden, 1958 (Cameroon), Pseudolerida incerta (Equatorial Guinea: Bioko Island, Tanzania, Uganda); Myrocheini: Humria bimaculicollis Linnavuori, 1975 (Botswana, Democratic Republic of the Congo, Guinea, Kenya, Mozambique, Namibia, South Africa, Zambia, Zimbabwe); Strachiini: Afrania brachyptera (Schaum, 1853) (Botswana, Democratic Republic of the Congo; Tanzania: Tanganyika, Zanzibar; Uganda). Variability of Tripanda jurickorum, Pseudolerida incerta and Humria bimaculicollis is discussed.